2017
DOI: 10.1016/j.kint.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 drives abnormal proliferation in autosomal dominant polycystic kidney disease

Abstract: Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 47 publications
5
54
0
Order By: Relevance
“…JAK-STAT is an evolutionarily conserved pathway misregulated in a number of conditions such as cancer, arthritis and other inflammatory diseases 4 . We, and others, have previously shown that this pathway is abnormally activated in, and contributes to, ADPKD 5-9 . The pathway becomes activated by a series of tyrosine phosphorylation steps mediated by one of the four kinases JAK1-JAK3 or Tyk2.…”
Section: Introductionmentioning
confidence: 71%
“…JAK-STAT is an evolutionarily conserved pathway misregulated in a number of conditions such as cancer, arthritis and other inflammatory diseases 4 . We, and others, have previously shown that this pathway is abnormally activated in, and contributes to, ADPKD 5-9 . The pathway becomes activated by a series of tyrosine phosphorylation steps mediated by one of the four kinases JAK1-JAK3 or Tyk2.…”
Section: Introductionmentioning
confidence: 71%
“…Mechanistically we identify that ANKHD1 alters proliferative signalling by enhancing STAT5-driven transcription in ADPKD kidneys. This is interesting since it was recently shown that STAT5 is a major contributor to proliferation and ADPKD disease progression 18 . The fact that ANKHD1 drives proliferation and enhances fibrogenesis together suggest that it is an ideal future therapeutic target, since its successful inhibition is predicted to block both the growth of cysts and inhibit tissue scarring, which is a final common pathway to organ failure irrespective of the initial cause of damage.…”
Section: Discussionmentioning
confidence: 99%
“…ANKHD1 enhances ADPKD proliferation by promoting STAT5 signalling. It was previously reported that ADPKD is characterised by altered JAK/STAT signalling and specifically STAT5 is elevated in polycystic kidneys 18 . Our previous RNA-seq data illustrated that ANKHD1 alters JAK/STAT activity, therefore, to investigate a potential role of Ankhd1 in the control of STAT5 signalling, we used mice with targeted Ankhd1deficiency in the Pkd1 nl/nl model of polycystic kidney disease.…”
Section: Ankhd1 Silencing Reduces Proliferation Potential In Human Pamentioning
confidence: 99%
See 2 more Smart Citations